Prevalence and prognostic impact of diabetes in takotsubo syndrome: insights from the international, multicenter GEIST registry - Stiermaier, Thomas; Santoro, Francesco; El-Battrawy, Ibrahim; Möller, Christian; Graf, Tobias; Novo, Giuseppina; Santangelo, Andrea; Mariano, Enrica; Romeo, Francesco; Caldarola, Pasquale; Fanelli, Mario; Thiele, Holger; et al. (Diabetes care, 2018)
OBJECTIVE: In view of low prevalence rates, diabetes is discussed as a protective factor for the occurrence of Takotsubo syndrome (TTS). Furthermore, it was associated with improved outcome in a small single-center analysis. Therefore, this study assessed the prevalence and prognostic relevance of concomitant diabetes in TTS. - RESEARCH DESIGN AND METHODS: A total of 826 patients with TTS were enrolled in an international, multicenter, registry-based study (eight centers in Italy and Germany). All-cause mortality was compared between patients with diabetes and patients without diabetes, and the independent predictive value of diabetes was evaluated in multivariate regression analysis. - RESULTS: The prevalence of diabetes was 21.1% (n = 174). TTS patients with diabetes were older (P < 0.001), were more frequently male (P = 0.003), had a higher prevalence of hypertension (P < 0.001), physical triggers (P = 0.041), and typical apical ballooning (P = 0.010), had a lower left ventricular ejection fraction (P = 0.008), had a higher rate of pulmonary edema (P = 0.032), and had a longer hospital stay (P = 0.009). However, 28-day all-cause mortality did not differ between patients with diabetes and patients without diabetes (6.4% vs. 5.7%; hazard ratio [HR] 1.11 [95% CI 0.55-2.25]; P = 0.772). Longer-term follow-up after a median of 2.5 years revealed a significantly higher mortality among TTS patients with diabetes (31.4% vs. 16.5%; P < 0.001), and multivariate regression analysis identified diabetes as an independent predictor of adverse outcome (HR 1.66 [95% CI 1.16-2.39]; P = 0.006). - CONCLUSIONS: Diabetes is not uncommon in patients with TTS, is associated with increased longer-term mortality rates, and is an independent predictor of adverse outcome irrespective of additional risk factors.